0319 Sleep Architecture and Neurocognitive and Behavioral Functioning in Youth from the General Population. (27th May 2020) - Ricci, A; Fang, J; He, F; Cain, P; Calhoun, S L; Liao, D; Vgontzas, A N; Bixler, E O; Fernandez-Mendoza, J
Abstract: Introduction: The transition from childhood to adolescence is critical for the onset of psychopathology and reflects significant changes in the sleeping brain. Sleep deprivation studies have shown that rapid eye movement (REM) and non-rapid eye movement (NREM) sleep are differentially involved in specific cognitive functions. The aim of this study was to examine the association of sleep architecture with neurobehavioral outcomes in a population-based sample. Methods: We studied 700 children (5-12y, 47.1% female, 23.7% minority) and 421 adolescents (12-23y, 46.1% female, 21.8% minority) from the Penn State Child Cohort. All subjects underwent a 9-hour polysomnography and a 4-hour neurobehavioral evaluation. Neurocognitive outcomes included the Stroop test, digit span backwards (DSB), and coding to measure high- and low-order cognitive functions. Behavioral outcomes included the Child/Adult Behavior Checklist to measure internalizing symptoms and externalizing behaviors. Correlation analysis examined the cross-sectional association between sleep architecture and neurocognitive and behavioral outcomes. Results: In childhood, %REM sleep was negatively associated with DSB scores (r=-0.088, p=0.027), particularly in males (r=-0.167, p=0.002). Furthermore, %NREM sleep was positively associated with DSB scores in males (r=0.126, p=0.021). In adolescent females, %NREM and %REM sleep were positively (r=0.146, p=0.044) and negatively (r=-0.158, p=0.029) associated with DSB scores, respectively. In adolescence, %NREM sleep was negatively associated with internalizing symptoms (r=-0.109, p=0.026). Conclusion: Male children and female adolescents who spent a higher proportion of the night in NREM sleep had better working memory performance. Adolescent females who spent a lower proportion of the night in NREM sleep had greater internalizing symptoms. This study suggests a role for sleep architecture in neurobehavioral deficits in youth. Future studies are necessary to determine the contributions of low- and high-frequency sleep EEG dynamics to these clinical outcomes. Support: National Institutes of Health (R01MH118308, R01HL97165, R01HL63772, UL1TR000127)